21st century literature from the philippines and the world - Marikit Uychoco (Quezon City : Rex Book Store, Inc., 2022)
"The third edition features new literary text , social- emotional learning points, and summative assessments that can be used in preparation for the collage entrance exams. This work text aims to help students understand the complex world they are living in through the use of literature."
Includes bibliography and index.
English text.